1996
DOI: 10.1128/jvi.70.6.4150-4156.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that replication of human neurotropic JC virus DNA in glial cells is regulated by the sequence-specific single-stranded DNA-binding protein Pur alpha

Abstract: Initiation of polyomavirus DNA replication in eukaryotic cells requires the participation of the viral early protein T antigen, cellular replication factors, and DNA polymerases. The human polyomavirus JC virus (JCV) is the etiologic agent of the fatal demyelinating disease progressive multifocal leukoencephalopathy in immunocompromised individuals. This virus exhibits a narrow host range and a tissue specificity that restricts its replication to glial cells of the central nervous system. Restriction of viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Pura in the absence of Tat inhibit initiation (Chang et al, 1996). It has previously been observed that Tat of clade B has little effect on the JCV ori in the absence of added Pura in KG-1C cells.…”
Section: Differences In Kg-1c Cell Smad4 Mrna Levels In Response To Tmentioning
confidence: 85%
See 1 more Smart Citation
“…Pura in the absence of Tat inhibit initiation (Chang et al, 1996). It has previously been observed that Tat of clade B has little effect on the JCV ori in the absence of added Pura in KG-1C cells.…”
Section: Differences In Kg-1c Cell Smad4 Mrna Levels In Response To Tmentioning
confidence: 85%
“…Tat is avidly incorporated by oligodendrocytes (Daniel et al, 2004), where it can exert positive control over both transcription (Krachmarov et al, 1996) and replication (Daniel et al, 2001) of JCV DNA. Tat does not bind directly to JCV DNA, but it interacts with cellular proteins and protein complexes that bind to sequences in the JCV non-coding control region (NCCR) (Chang et al, 1994(Chang et al, , 1996Chen et al, 1995;Daniel et al, 2001Daniel et al, , 2004Gallia et al, 1998Gallia et al, , 1999. The NCCR contains the origin of JCV DNA replication (ori) as well as promoter sequences for both JCV early (E) and late (L) gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…We next asked, using this fractionation scheme, with what fractions did cytoskeletal components and a nuclear protein, pur ␣ (Chang et al, 1996), elute. Pur ␣ was measured because we observed ODC in the nucleus in many micrographs; therefore, "insoluble" ODC activity could be caused by delayed lysis of the keratinocyte nucleus.…”
Section: Subcellular Fractionation Of Nhek By Detergent and Salt Extrmentioning
confidence: 99%
“…The viral lytic cycle begins with expression of the viral early protein, T antigen, which occurs before replication of the viral DNA. T antigen is a multifunctional protein which interacts with several host regulatory proteins and, by manipulating host gene expression and/or function, orchestrates subsequent steps of the viral life cycle including viral DNA replication (4) and activation of late gene transcription (17). The products of the late genes, the capsid proteins, accumulate in the nucleus and associate with the replicated viral DNA-forming virions which, in turn, lyse the host oligodendrocytes.…”
mentioning
confidence: 99%